SOME AMERICAN, POLISH, GERMAN, CZECH AND SORBIAN PROVERBS ABOUT A WOMAN’S PLACE AND THEIR HISTORICAL AND CULTURAL CONTEXT - Deutsch, Emilia Anna (Proverbium - Yearbook, 2022)
This paper will concentrate firstly on American and European culture in the 19th and 20th centuries to illustrate the cultural context in which proverbs about women were used, which refer to the following themes: women’s work, a woman’s place is in the home and a woman makes a home, a man needs a woman, and smart women were then put to use. The main aim of the article is to show briefly the correlation between the history and culture of women in the U.S.A. and in Central and Eastern Europe (where the German, Polish, Czech and Sorbian languages were used) and the position of women in some American, German, Polish, Czech and Sorbian proverbs. The language material of this article is confirmed by statements from women who lived in the nineteenth century and also with scientific publications about women’s place in society until now.